Characterization of the aroma profiles of cold and hot break tomato pastes by GC-O-MS, GC × GC-O-TOF-MS, and GC-IMS. (30th March 2023) - Li, Xuejie; Zeng, Xiangquan; Song, Huanlu; Xi, Yu; Li, Yan; Hui, Bowen; Li, He; Li, Jian
Highlights: Total of 274 volatile compounds were identified in CB and HB tomato pastes. The aroma compounds extracted by SAFE in CB tomato paste were more abundant than HB. 10 aroma-active compounds were detected for the first time in tomato pastes. 9 volatiles were identified for the first time in tomato pastes. More compounds were identified using GC × GC-O-TOF-MS compared with GC-O-MS. Abstract: GC × GC-O-TOF-MS and GC-IMS have attracted increasing attention in complex food flavor analysis due to their high resolution and sensitivity. However, very few studies have attempted to identify the aroma components of tomato pastes through these techniques. Herein, the present study comprehensively characterized the aroma profiles of cold and hot break tomato pastes using SAFE-GC-O-MS, SAFE-GC × GC-O-TOF-MS, and HS-GC-IMS for the first time. A total of 274 volatile compounds were identified, far more than previously reported. About 87 % of these compounds can be identified by GC × GC-O-TOF-MS, exceeding 6 times that of GC-O-MS. Notably, 10 aroma-active compounds and 9 volatiles were identified by GC × GC-O-TOF-MS and HS-GC-IMS for the first time. The AEDA and OAVs results indicated that β -damascenone, linalool, 3-ethylbutanoic acid, and nonanal were the most powerful aroma-active compounds. These findings will provide deeper insights into improving the sensory quality of tomato paste.